Determinants and Solutions for Youth Unemployment in East Java Province in 2023 - Ayu Istiqomah; Wahyu Hidayat Riyanto; FX Gugus Febri Putranto; Muhammad Firmansyah (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2026)
Youth unemployment remains a problem in East Java Province. This study aims to analyse the determinants of youth unemployment in East Java Province in 2023. Secondary data from the 2023 National Labor Force Survey (Sakernas), with individual-level observations, were analysed using binary logistic regression. The results showed that gender, marital status, education level, age, work experience, the district/city minimum wage (UMK), and economic growth significantly affected youth unemployment. Synchronisation is needed between the education system and market needs so that graduates can enter the workforce immediately. In addition, quality and inclusive economic growth are essential in increasing youth labour absorption.